1998
DOI: 10.2105/ajph.88.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Rates and independent correlates of Pap smear testing among Korean-American women.

Abstract: OBJECTIVES: This study reports population estimates of Pap smear testing among Korean-American women and evaluates correlates of testing. METHODS: Korean Americans in 2 California counties were surveyed by telephone. Frequencies were age-adjusted to the 1990 census to produce population estimates of testing. Logistic regression models were used to evaluate independent correlates of testing RESULTS: Only 50% of the Korean-American women surveyed had a Pap test in the previous 2 years. The strongest independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 4 publications
2
35
1
1
Order By: Relevance
“…We found that some of the independent variables were significant predictors of both outcome measures, which is consistent with findings from literature (Juon, Choi, & Kim, 2000;Juon et al, 2002;Juon et al, 2003;K. Kim et al, 1999;Wismer et al, 1998). Such variables included, for example, age, marital status, income, having knowledge of the early detection method for cervical cancer, and perceived beliefs about benefits of and barriers to receiving Pap testing.…”
Section: Discussionsupporting
confidence: 89%
“…We found that some of the independent variables were significant predictors of both outcome measures, which is consistent with findings from literature (Juon, Choi, & Kim, 2000;Juon et al, 2002;Juon et al, 2003;K. Kim et al, 1999;Wismer et al, 1998). Such variables included, for example, age, marital status, income, having knowledge of the early detection method for cervical cancer, and perceived beliefs about benefits of and barriers to receiving Pap testing.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings reported among the Norwegian female physicians, significant correlates of Pap smear screening were being married [68]. Similarly, study among the Korean-American women showed the strongest correlates of Pap smear with marital status [69].…”
Section: Discussionsupporting
confidence: 82%
“…Studies in other countries have also found a close association between Pap smear screening and health care utilization indicators [34,69,70].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Studies have reported that only 22%-75% of Korean American women had ever had a Papanicolaou (Pap) test, and only 26%-63% had had the test in the prior two to three years (Juon, Choi, & Kim, 2000;Juon, Seung-Lee, & Klassen, 2003;Kim et al, 1999;Moskavitz, Kazinets, Tager, & Wong, 2004;Sarna, Tae, Kim, Brecht, & Maxwell, 2001;Wismer et al, 1998b). Their Pap screening rates are far lower than the age-adjusted rates from a national random sample, the 1999 Behavioral Risk Factor Surveillance System (BRFSS), which found that 94% of women aged 18 years and older with an intact cervix had ever had a Pap test and 84% had had one in the prior three years (Coughlin, Uhler, Hall, & Briss, 2004).…”
Section: Key Pointsmentioning
confidence: 99%